Design principles for result-based, collective and value chain-based environment and climate contract solutions in agriculture and forestry: Learning from 44 case studies across Europe - T. Eichhorn; T. Runge; D. Viaggi; J. Kantelhardt; F. Bartolini; T. Bradfield; P. Dupraz; K.S. Harmanny; A. Iglesias; F. Le Gloux; E. Majewski; A. Malak-Rawlikowska; et al. (Land Use Policy, 2026)

Implications of gear selection for monitoring benthic fish communities in the Beaufort Sea - Duane E. Stevenson; Stan Kotwicki; Brenda Norcross; Andrew Majewski (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sediment analysis and historical context of the 2018 Palu-Donggala tsunami deposit, Indonesia - Jędrzej M. Majewski; Adam D. Switzer; Rachel Y.S. Guan; Benazir Benazir; Ella Meilianda; Peter R. Parham; Robert Weiss; Stacey S. Martin; Lillian K. Pearson; Jessica E. Pilarczyk; Patrick Daly; Benjamin P. Horton (Marine Geology, 2023)

Cod movement ecology in a warming world: Circumpolar arctic gadids - Harri Pettitt‐Wade; Lisa L. Loseto; Andrew Majewski; Nigel E. Hussey (Fish and Fisheries, 2021)
Understanding fish movement in the Arctic is paramount during the current era of rapidly warming seas, receding sea ice and associated shifting species distributions and fishing effort. We synthesized the literature and identified key knowledge gaps on the movement ecology of Arctic cod ( Boreogadus saida ) and Polar/Ice cod ( Arctogadus glacialis , both Gadidae) in the context of climate change. Standardized web‐based English‐language literature searches yielded 51 articles directly relevant and 122 indirectly relevant for the movement ecology of these species combined. Most articles were primarily relevant to B. saida (85% of total filtered articles), occurred during open water season (49/38%) with focus on distribution (32/22%), predators (30/22%), seasonal spawning/feeding movements (22/19%), sea ice association (22/26%), climate change (20/15%) and vertical movements (17/19%) with few focused on horizontal dynamics (3/0%; B . saida / A . glacialis , respectively). Disproportionate data resolution has resulted in greater predictive power of movement models for the European (29% of articles) and North American (86%) Arctic regions relative to the logistically challenging Central Arctic Ocean and Russian‐Siberian Arctic shelves (both 7%). The movements of circumpolar Arctic gadids are dependent on complex dynamics that include regional currents, the longevity of ice‐flows and polynyas, water stratification and coastal hydrology. Dependence on these interactive and often co‐dependent processes highlights major pathways and barriers to movement and distribution at higher latitudes. Despite a recent increase in impactful research, there is a critical need for more direct research on circumpolar gadid movements to aid understanding of climate change impacts on Arctic ecosystems and fisheries.

Mitochondrial genome diversity and population mitogenomics of polar cod (Boreogadus saida) and Arctic dwelling gadoids - Robert E. Wilson; Sarah A. Sonsthagen; Noel Smé; A. J. Gharrett; Andrew R. Majewski; Kate Wedemeyer; R. John Nelson; Sandra L. Talbot (Polar Biology, 2020)

Conference Report: 22nd ETH Conference on Combustion Generated Nanoparticles - Hannu E. Jääskeläinen; W. Addy Majewski (Emission Control Science and Technology, 2019)

A comparison of the trophic ecology of Beaufort Sea Gadidae using fatty acids and stable isotopes - J. D. Brewster; C. Giraldo; E. S. Choy; S. A. MacPhee; C. Hoover; B. Lynn; D. G. McNicholl; A. Majewski; B. Rosenberg; M. Power; J. D. Reist; L. L. Loseto (Polar Biology, 2018)

Changes in chemical coding of sympathetic chain ganglia (SChG) neurons supplying porcine urinary bladder after botulinum toxin (BTX) treatment - E. Lepiarczyk; A. Bossowska; M. Majewski (Cell and Tissue Research, 2015)

A novel rearrangement of occludin causes brain calcification and renal dysfunction - Marissa A. LeBlanc; Lynette S. Penney; Daniel Gaston; Yuhao Shi; Erika Aberg; Mathew Nightingale; Haiyan Jiang; Roxanne M. Gillett; Somayyeh Fahiminiya; Christine Macgillivray; Ellen P. Wood; Philip D. Acott; et al. (Human Genetics, 2013)

Campylobacter protein oxidation influences epithelial cell invasion or intracellular survival as well as intestinal tract colonization in chickens - A. M. Łasica; A. Wyszyńska; K. Szymanek; P. Majewski; E. K. Jagusztyn-Krynicka (Journal of Applied Genetics, 2010)

Postimpoundment Time Course of Increased Mercury Concentrations in Fish in Hydroelectric Reservoirs of Northern Manitoba, Canada - R. A. Bodaly; W. A. Jansen; A. R. Majewski; R. J. P. Fudge; N. E. Strange; A. J. Derksen; D. J. Green (Archives of Environmental Contamination and Toxicology, 2007)

Book Reviews - Eric L. Geist; E. Majewski; Tracy Rushmer; Marek Lewandowski; Wayne Robertson; Daniel Wójcik; Jacek Leliwa-Kopystynski; Krzysztof Haman (Pure and Applied Geophysics, 1997)